PELUANG KOTA MENUJU PEMBANGUNAN YANG BERKELANJUTAN DALAM RANGKA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Pujiati, Amin (Proceeding SENDI_U, 2015)
The Development of the present national and regional done aiming at improving the well-being of the community.Execution of development can not be inevitable from the use of natural resources. However, the exploitation ofnatural resources which are not heeding the abilities and resources support neighborhood resulted in adeterioration in the quality of the environment. It is necessary to research on the opportunities of the city towardssustainable development in order to improve the welfare of society. This study aims to measure the probability of thecity towards sustainable development based on the classification of cities in Urban Semarang and yogyakarta.Analysis tool used is the multinomial logistic regression. The results showed the economic factors, demographic andsocial factors that influence the classification of the city towards sustainable development. City inhabitants are solidprobabilities to become a sustainable city is getting smaller. Calculation probabilities through scenario data,mapping can be used in the future and the basis of decision-making or the determination of urban policies relatingto the environment.Key words: probability, city, sustainable, scenario, binary logistic regression